(untitled) (Circe de clásicos y modernos, 2021)
In this text we address the problem of existing sources and their analysis methodologies for the study of the great slave revolts in the Roman Republic. Our aim is to elucidate the different types of available sources we have and their states of conservation; pointing out the difficulties and heuristic possibilities they present; and analyzing them from a historiographic point of view. Although most of them, and the literary ones in their totality, come from the citizen elite, and consequently they express the point of view of the winners, hostile to the servile revolt, and it imply partiality, distortion and concealment in the historical record, we argue that it is not convenient to exaggerate their bias as a limiting factor of the knowledge of the facts. On the one hand, it is possible to extract valuable information about the rebel slaves from the narrative sources; on the other hand, some material sources produced by the rebels are also preserved. All of which allows us to at least glimpse the vision of the vanquished.